A Highly Active Molybdenum Phosphide Catalyst for Methanol Synthesis from CO and CO2. Issue 46 (18th October 2018) - Duyar, Melis S.; Tsai, Charlie; Snider, Jonathan L.; Singh, Joseph A.; Gallo, Alessandro; Yoo, Jong Suk; Medford, Andrew J.; Abild‐Pedersen, Frank; Studt, Felix; Kibsgaard, Jakob; Bent, Stacey F.; Nørskov, Jens K.; et al.
Abstract: Methanol is a major fuel and chemical feedstock currently produced from syngas, a CO/CO2 /H2 mixture. Herein we identify formate binding strength as a key parameter limiting the activity and stability of known catalysts for methanol synthesis in the presence of CO2 . We present a molybdenum phosphide catalyst for CO and CO2 reduction to methanol, which through a weaker interaction with formate, can improve the activity and stability of methanol synthesis catalysts in a wide range of CO/CO2 /H2 feeds. Abstract : MoP‐ed up : MoP is a new catalyst for CO and CO2 hydrogenation to methanol. By stabilizing only the monodentate binding configuration of formate, the phosphide is able to circumvent the (scaling) relationship between the necessary ability of the catalyst to bind oxygen‐containing intermediates and catalyst deactivation resulting from high formate coverage in the presence of CO2 .